2021
DOI: 10.2166/ws.2021.239
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of the effect of asymmetric-lattice collar shape and placement on scour depth and flow pattern around a bridge pier

Abstract: In this study, the effect of collar shape and its alignment on reducing scour depth in the front part of the structure, with the pier under clear water conditions, was investigated to determine changes in the flow pattern around the structure. The collars were examined in two asymmetrical shapes with dimensions of and at three levels of installation relative to the bed: bed level, 1 and 2 cm above the bed. The results revealed that the presence of the collar not only reduced the ultimate scouring depth but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Compared with a circular collar, a rectangular collar has better protection to the sediment surface; it reduces maximum scour depth around piers by 79%. Raeisi and Ghomeshi [16] proposed an elliptical collar to weaken the downstream vortex through interference on the water flow downstream of the bridge pier, which has better performance than the ordinary circular collar. For the three-dimensional collar, Bestawy et al [17] developed a conical collar, which was found to have a good effect on reducing scour around the pier through a single pier model experiment, and the scour depth downstream side of the pier was reduced by 61.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a circular collar, a rectangular collar has better protection to the sediment surface; it reduces maximum scour depth around piers by 79%. Raeisi and Ghomeshi [16] proposed an elliptical collar to weaken the downstream vortex through interference on the water flow downstream of the bridge pier, which has better performance than the ordinary circular collar. For the three-dimensional collar, Bestawy et al [17] developed a conical collar, which was found to have a good effect on reducing scour around the pier through a single pier model experiment, and the scour depth downstream side of the pier was reduced by 61.1%.…”
Section: Introductionmentioning
confidence: 99%